Letter: hepatocellular carcinoma negatively affects sustained virological response of direct‐acting anti‐viral treatment in decompensated cirrhosis. Issue 8 (7th October 2019) - He, Caini; Li, Shen; Zhao, Yunyu; Ji, Fanpu
Abstract : LINKED CONTENT This article is linked to Mecci et al paper. To view this article, visithttps://doi.org/10.1111/apt.15296 .